DataBurst: Interactive analysis of hierarchical data using radial space-filling diagrams - Smith, Christopher Ravi (Dalhousie University, Halifax, 2010)
Radial visualization methods have been used frequently in the field of information visualization due to their compact design and aesthetic layout of data items that can often aid in the communication of relationships between them. Published methods however offer varying levels of effectiveness and are often restricted to particular data types, perspectives and interfaces that may not facilitate detailed data investigation or allow for knowledge discovery outside of what was originally intended when the visualization was developed. We present DataBurst, an open, flexible data visualization that extends traditional concentric radial space-filling diagrams using two methods of Focus+Context and uniquely leverages three radial diagram characteristics. DataBurst's effectiveness with varying volumes and types of data is then shown with two case studies and show that insight can be quickly gained by interactively viewing up to three attributes of data at once in the context of the hierarchy of the data.